A4_7 Spinning Worlds - Nuttall, Heather; Coulson, Rebecca; Sier, Anya; Shehzad, Habeebah; Wayman, James (Physics Special Topics, 2022)
In this paper how the centripetal force changes over latitude is investigated for the different planets in our solar system. It is found that Venus has the smallest centripetal force, while Earth has the largest centripetal force. For all the planets the centripetal force is found to be at a maximum at the equator and decreasing to a minimum at the pole.